Evaluasi Stabilitas dan Adaptabilitas Karakter Agronomi Kedelai (Glycine max L. Merrill) dalam Respon Interaksi Genotip dengan Lingkungan - Anjelina, Patimah (Jurnal Kridatama Sains dan Teknologi, 2025)
Soybeans are a strategic national commodity that plays an important role in food security. However, domestic production of high-quality soybeans remains low, leading to high dependence on imports. One strategy to reduce soybean imports is through a plant breeding program, which aims to produce high-yielding soybean varieties that can adapt well to various agroecological conditions. However, in practice, soybean breeders often face diverse soil conditions, which can cause instability in soybean performance. This study aims to evaluate the stability and adaptability of 14 soybean genotypes based on their phenotypic responses to three different environments. The parameters observed include plant height, flowering time, number of pods per plant, and number of seeds per plant. Analysis was conducted using the Eberhart and Russell stability model, considering the regression coefficient (bi), deviation from regression (Sd²), and standard error SE(bi). Results indicated significant genotype-environment interactions, reflecting the instability of some genotypes to changes in environmental conditions. The genotypes Detap 1, Detam 3 Prida, and Galur 122 showed high stability and broad adaptability across several agronomic traits, while the genotypes Wilis, Galur 106, and Devon 1 were classified as unstable with significant deviation values. Some genotypes, such as Anjasmoro and Devon 2, exhibited good stability but had more specific adaptability to certain environments. The results of this study provide a strong scientific basis for soybean variety selection, thereby improving land use efficiency, supporting consistent production planning, and reducing the risk of yield decline due to variety unsuitability to the growing environment